Distributed Drug Discovery, Part 3: using D(3) methodology to synthesize analogs of an anti-melanoma compound - Scott, William L; Audu, Christopher O; Dage, Jeffery L; Goodwin, Lawrence A; Martynow, Jacek G; Platt, Laura K; Smith, Judith G; Strong, Andrew T; Wickizer, Kirk; Woerly, Eric M; O'Donnell, Martin J (Journal of combinatorial chemistry, 2009)
For the successful implementation of Distributed Drug Discovery (D(3)) (outlined in the accompanying Perspective), students, in the course of their educational laboratories, must be able to reproducibly make new, high quality, molecules with potential for biological activity. This article reports the successful achievement of this goal. Using previously rehearsed alkylating agents, students in a second semester organic chemistry laboratory performed a solid-phase combinatorial chemistry experiment in which they made 38 new analogs of the most potent member of a class of antimelanoma compounds. All compounds were made in duplicate, purified by silica gel chromatography, and characterized by NMR and LC/MS. As a continuing part of the Distributed Drug Discovery program, a virtual D(3) catalog based on this work was then enumerated and is made freely available to the global scientific community.